Kajian Fisis pada Gerak Osilasi Harmonis - Esmar Budi (Universitas Negeri Jakarta, 2015)
Abstract This article explain the study on a simple harmonic oscillation. The study was conducted through laboratory experiments on simple oscillatory motion on the system as well as the physical pendulum spring-mass system, using experimental tools JEULIN device equipped with a Generis+5 software. Results of this experiments on oscillatory motion of a physical pendulum system shows that the simple harmonic oscillation is met if the initial deflection system is small (<100). As for the spring-mass system, simple harmonic oscillation properties are determined by the value of the spring constant of the system and the mass of the system load. The amplitude oscillatory motion increases with increasing system load. Keywords: simple oscillatory motion, angle of deviation, the system physical pendulum, spring-mass system, amplitude, period. Abstrak Artikel ini memuat kajian pada osilasi harmonis sederhana. Kajian dilakukan melalui kegiatan percobaan di laboratorium pada gerak osilasi sederhana pada sistem bandul fisis serta sistem pegas-massa, menggunakan perangkat alat percobaan Jeulin berbantuan komputer yang dilengkapi dengan perangkat lunak Generis+5. Hasil percobaan pada gerak osilasi sistem bandul fisis menunjukan bahwa osilasi harmonis sederhana terpenuhi jika simpangan awal sistem adalah kecil (<100). Sedangkan untuk sistem pegas-massa, sifat osilasi harmonis sederhana ditentukan oleh nilai tetapan pegas sistem dan massa beban sistem. Amplitudo gerak osilasi meningkat seiring dengan peningkatan beban sistem. Kata-kata kunci: gerak osilasi sederhana, sudut simpangan, sistem bandul fisis, sistem pegas-massa, amplitudo, perioda.